Islamic Education and Civilization During the Khulafaur Rasyidin: A Historical Analysis - Alda Alda; Wahyuni Wahyuni; A. Widya Asih Muhammad; Maman Roestaman; Agus Susilo; Supriandi Supriandi (Early Publishing, 2026)
The Khulafaur Rasyidin period represents a crucial phase in the history of Islamic civilization following the death of Prophet Muhammad (PBUH), spanning from 632 to 661 CE. This era was led by four caliphs: Abu Bakr Ash-Shiddiq, Umar ibn Khattab, Uthman ibn Affan, and Ali ibn Abi Talib. Their leadership played a significant role in preserving the unity of the Muslim community, expanding Islamic territories, and establishing a governance system based on the values of justice, consultation (shura), and Islamic teachings. Moreover, this period marked the early development of administrative and legal systems that became the foundation for the subsequent growth of Islamic civilization. Therefore, the Khulafaur Rasyidin era is regarded as an ideal model of Islamic leadership that remains relevant as a reference for social and political life in the modern era. In addition, the Khulafaur Rasyidin period illustrates the successful integration of religious principles with political governance, creating a balanced and stable societal structure. The legacy of this era continues to influence contemporary discussions on ethical leadership, governance, and social justice within both Islamic and global contexts. Apart from building a government system, Khulafaur Rasyidin's time was also an important period in the development of Islamic education through strengthening the learning of the Koran, hadith, moral development, sending teachers to various regions, as well as the codification of the Al-Qur'an mushaf which became the foundation for development. Islamic education in the future.